Cortisol salivar na avaliação do eixo hipotálamo-hipofisário-adrenal em crianças saudáveis menores de 3 anos Salivary cortisol to assess the hypothalamic-pituitary-adrenal axisin healthy children under 3 years old - Margarete L. Silva; Márcia C. Mallozi; Giesela F. Ferrari (Jornal de Pediatria, 2007)
OBJETIVO: Estabelecer intervalos de concentrações referenciais de cortisol salivar em crianças saudáveis, nos períodos matutino e vespertino, verificando os fatores de interferência nessa dosagem e a possibilidade de presença de ritmo circadiano. MÉTODOS: Pesquisa observacional controlada, incluindo aleatoriamente 91 crianças com idade de 45 dias a 36 meses, residentes em comunidade de Santo André (SP). Critérios de inclusão: nutridas, saudáveis, sem febre ou uso de corticóide, subdivididas em faixas etárias (cinco subgrupos) com intervalo de 6 meses. Houve coleta de saliva domiciliar nos períodos manhã e tarde para dosagem de cortisol, sob radioimunoensaio com anticortisol 3-oxima-albumina bovina. RESULTADOS: Os cinco subgrupos apresentaram dosagens matutinas superiores às vespertinas (p < 0,001), com diferença superior a 30% a partir de 1 ano de idade. Valor médio em nmol/L foi de 557,86 (manhã) e 346,36 (tarde). Observou-se correlação linear negativa na dosagem matutina para horas de repouso e freqüência de dieta (p < 0,05); na vespertina, para medidas antropométricas (p < 0,05). CONCLUSÕES Foram estabelecidos valores de referência de normalidade de cortisol salivar em crianças saudáveis, e aos 45 dias foi possível observar ritmo circadiano, que atingiu maturidade aos 12 meses de vida. Privações de sono e dieta elevaram valores de cortisol matutino. OBJECTIVE: To establish reference concentration intervals for salivary cortisol in healthy children, in the morning and in the afternoon, investigating factors that interfere with the concentration measured and the possibility that circadian rhythms are present. METHODS: A controlled observational study was carried out with 91 children aged 45 days to 36 months, selected at random and living in Santo André, state of São Paulo, Brazil. Inclusion criteria were: healthy, well-nourished, free from fever and corticoid use, subdivided by age group (five subsets) at 6-month intervals. Saliva was collected during home visits in the morning and afternoon. Cortisol was radioimmunoassayed with cortisol 3-oxime-bovine albumin antiserum. RESULTS: The five subsets exhibited higher cortisol concentration during the morning than in the afternoon (p < 0.001), and this difference passed 30% from 1 year of age onwards. Mean concentrations, in nmol/L, were 557.86 (morning) and 346.36 (afternoon). A negative linear correlation was observed between morning concentrations and hours' sleep and frequency of meals (p < 0.05), and in the afternoon with anthropometric measurements (p < 0.05). CONCLUSIONS: Reference values for normal salivary cortisol in healthy children were established. At 45 days it was possible to observe circadian rhythms, which reached maturity at 12 months of life. Sleep and food deprivation increased morning cortisol levels.